Adelaide Ristori’s manuscript and the published text of Dom Pedro II translation about the Episode of Count Ugolino of The Divine Comedy: which represents the desire of author? - Daros, Romeu Porto (Manuscrítica: Revista de Crítica Genética, 2018)
Emperor Dom Pedro II from Brazil, as well as head of state, had a remarkable interest in the Arts and Literature and was aware of their importance for the political and cultural consolidation of the nation in the postcolonial context of a country in formation. In the world of Letters he showed particular appreciation for the work of Dante Alighieri, whose study and translation were tasks he had undertaken from an early age. His translations of the Divine Comedy were published in 1889 and are considered, until then, the final texts of these. However, in my study of the manuscripts of the Monarch's translation of Count Ugolino's episode, from corner XXXIII of "Inferno," I attached to the genetic file an autograph which he had sent to the actress Adelaide Ristori in 1869. The comparative analysis of this manuscript with the other autographs and the text published in 1889 raised doubts as to whether this really is the Emperor's final deed. Thus, in reviewing the creative process of Dom Pedro II and the data that the study points out, the objective of this article is to shed light on the question of which of these two texts represents the will of the author.